Stretchable Electrochemical Sensor for Real-Time Monitoring of Cells and Tissues - Liu, Yan-Ling; Jin, Zi-He; Liu, Yan-Hong; Hu, Xue-Bo; Qin, Yu; Xu, Jia-Quan; Fan, Cui-Fang; Huang, Wei-Hua (Angewandte Chemie International Edition, 2016)
Stretchable electrochemical sensors are conceivably a powerful technique that provides important chemical information to unravel elastic and curvilinear living body. However, no breakthrough was made in stretchable electrochemical device for biological detection. Herein, we synthesized Au nanotubes (NTs) with large aspect ratio to construct an effective stretchable electrochemical sensor. Interlacing network of Au NTs endows the sensor with desirable stability against mechanical deformation, and Au nanostructure provides excellent electrochemical performance and biocompatibility. This allows for the first time, real‐time electrochemical monitoring of mechanically sensitive cells on the sensor both in their stretching‐free and stretching states as well as sensing of the inner lining of blood vessels. The results demonstrate the great potential of this sensor in electrochemical detection of living body, opening a new window for stretchable electrochemical sensor in biological exploration. Biomedical sensor: A highly controllable strategy has been developed for synthesizing Au nanotubes with a large aspect ratio. The nanotubes were used to construct an effective stretchable electrochemical sensor and to realize real‐time monitoring of mechanically sensitive cells and tissues.